Variational method to the second-order impulsive PDE with non-periodic boundary value problems (II) - Bing Zhang; Jinting Guo; Bo Liu; Haichun Li (Proceedings of the 31st Chinese Control Conference, 2012)
By using the critical point theory of variational method and Lax-Milgram theorem, we obtain the new results for the existence of the solution of the second-order impulsive elliptic differential equations with non-periodic boundary value problems.